General Systemology Transdisciplinarity for Discovery, Insight and Innovation - Rousseau, David; Wilby, Jennifer; Billingham, Julie; Blachfellner, Stefan (Translational Systems Sciences, 2018)
XVII, 136 p. 32 illus., 25 illus. in color.